Air biomonitoring of heavy metals and polycyclic aromatic hydrocarbons near a cement plant - Baldantoni, Daniela; De Nicola, Flavia; Alfani, Anna (ATMOSPHERIC POLLUTION RESEARCH, 2014)
Biomonitoring studies, based on pollutant accumulation analyses in tree leaves, allow evaluating the impact caused by air-dispersed pollutants on ecosystems, providing useful data, complementary to those obtained by instrumental monitoring. In particular, leaves of sclerophylls present morphological characteristics, such as the presence of hairs and of a tick cuticle, making them particularly useful in bioaccumulation studies. The first aim of this research was to compare heavy metal (HM) and polycyclic aromatic hydrocarbon (PAH) leaf accumulation capabilities of two Mediterranean tree species. The second aim was to evaluate the impact of a cement plant and/ or of other anthropogenic activities occurring in industrial and urban areas on HM and PAH depositions. For these purposes, holm oak (Quercus ilex L.) and olive (Olea europaea L.) leaves collected along a transect industrial-urban-remote sites in southern Italy were employed. A different accumulation degree was observed for the two species. For HMs, Q. ilex leaves had the highest concentrations. The results showed that the influence of the cement plant emissions on pollutant concentrations was substantial in the area closer to clinker production and storage with the highest Pb, Ni, V, Cr, Fe, indeno(1,2,3-c, d) pyrene, benzo(g, h, i) perylene and benzo(a) anthracene leaf concentrations. However, Q. ilex leaves showed high HM and PAH concentrations also in the urban site, in relation to vehicular traffic emissions and depositions. The comparison of the results of the present study with those from the literature indicates that the overall air quality of the studied sites is not particularly compromised, also in proximity of the cement production. The use of holm oak should be preferred in biomonitoring due to its wider distribution compared to O. europaea.
The following values have no corresponding Zotero field: pub-location: DOKUZ EYLUL UNIV, DEPT ENVIRONMENTAL ENGINEERING, TINAZTEPE CAMPUS, BUCA, IZMIR 35160, TURKEY publisher: TURKISH NATL COMMITTEE AIR POLLUTION RES & CONTROL-TUNCAP
Keywords: industrial-urban-remote areas; leaf accumulation; Olea europaea L.; Quercus ilex L.

Effects of soil pollutants, biogeochemistry and microbiology on the distribution and composition of enchytraeid communities in urban and suburban holm oak stands - Rota, Emilia; Caruso, Tancredi; Monaci, Fabrizio; Baldantoni, Daniela; De Nicola, Flavia; Iovieno, Paola; Bargagli, Roberto (Environmental Pollution, 2013)
Holm oaks form typical urban woodlands in the Mediterranean region. We aimed at characterizing the enchytraeid communities in these environments and searching for possible correlations with soil pa- rameters, including the traffic contamination. Samples of litter and topsoil were collected at different spatial scales and seasons in Naples and Siena cities and in two suburban stands. Only the co-variation between pollution and other soil chemico-physical factors showed significant effects, whereas no direct effect of soil microbiology was detected. Some thermophilous Fridericia and Achaeta tolerate high con- centrations of heavy metals and PAHs and their abundance was mainly determined by Ca bioavailability. Central-European mesophilous species increased significantly under more temperate environmental conditions. Different combinations of soil cohesiveness, grain size composition and moisture regime seem to select species of certain body sizes. 
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Enchytraeids; Mediterranean urban communities; Microbiology; Pollutants; Soil biogeochemistry; terrestrial annelids

Effects of soil pollutants, biogeochemistry and microbiology on the distribution and composition of enchytraeid communities in urban and suburban holm oak stands - Rota, Emilia; Caruso, Tancredi; Monaci, Fabrizio; Baldantoni, Daniela; De Nicola, Flavia; Iovieno, Paola; Bargagli, Roberto (Environmental Pollution, 2013)
Holm oaks form typical urban woodlands in the Mediterranean region. We aimed at characterizing the enchytraeid communities in these environments and searching for possible correlations with soil pa- rameters, including the traffic contamination. Samples of litter and topsoil were collected at different spatial scales and seasons in Naples and Siena cities and in two suburban stands. Only the co-variation between pollution and other soil chemico-physical factors showed significant effects, whereas no direct effect of soil microbiology was detected. Some thermophilous Fridericia and Achaeta tolerate high con- centrations of heavy metals and PAHs and their abundance was mainly determined by Ca bioavailability. Central-European mesophilous species increased significantly under more temperate environmental conditions. Different combinations of soil cohesiveness, grain size composition and moisture regime seem to select species of certain body sizes. 
Keywords: Enchytraeids; Mediterranean urban communities; Microbiology; Pollutants; Soil biogeochemistry; terrestrial annelids

A multi-approach monitoring of particulate matter, metals and PAHs in an urban street canyon - De Nicola, Flavia; Murena, Fabio; Costagliola, M. Antonietta; Alfani, Anna; Baldantoni, Daniela; Prati, M. Vittoria; Sessa, Ludovica; Spagnuolo, Valeria; Giordano, Simonetta (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2013)
For the first time until now, the results from a prediction model (Atmospheric Dispersion Modelling System (ADMS)-Road) of pollutant dispersion in a street canyon were compared to the results obtained from biomonitors. In particular, the instrumental monitoring of particulate matter (PM10) and the biomonitoring of 14 polycyclic aromatic hydrocarbons (PAHs) and 11 metals by Quercus ilex leaves and Hypnum cupressiforme moss bags, acting as long- and short-term accumulators, respectively, were carried out. For both PAHs and metals, similar bioaccumulation trends were observed, with higher concentrations in biomonitors exposed at the leeward canyon side, affected by primary air vortex. The major pollutant accumulation at the leeward side was also predicted by the ADMS-Road model, on the basis of the prevailing wind direction that determines different exposure of the street canyon sides to pollutants emitted by vehicular traffic. A clear vertical (3, 6 and 9 m) distribution gradient of pollutants was not observed, so that both the model and biomonitoring results suggested that local air turbulences in the street canyon could contribute to uniform pollutant distribution at different heights.
The following values have no corresponding Zotero field: pub-location: TIERGARTENSTRASSE 17, D-69121 HEIDELBERG, GERMANY publisher: SPRINGER HEIDELBERG
Keywords: Holm oak leaves; metals; Moss bags; Naples urban area; PAHs; Pollutant dispersion model

Ozone fumigation of Quercus ilex L. slows down leaf litter decomposition with no detectable change in leaf composition - Baldantoni, Daniela; Bellino, Alessandro; Manes, Fausto; Alfani, Anna (ANNALS OF FOREST SCIENCE, 2013)
The evaluation of changes in litter decomposition rate due to increasing trend in tropospheric ozone is an emerging field of investigation, providing relevant information on long-term forest ecosystem sustainability. This research aims to clarify the effects of ozone exposure on Quercus ilex leaf chemical composition and decomposition slow down. Young plants were fumigated in growth chambers at a cumulative dose of 17.15 ppm h. To assess the fumigation effectiveness, stomatal conductance and net photosynthesis were monitored. Leaves were analysed for C, N, S, Ca, Mg, K, Fe, Zn, Mn, total soluble sugars, starch, acid-detergent fibre (ADF), lignin and cellulose prior to the incubation in litter bags in mesocosms, and during decomposition along 395 days. Ozone-exposed leaves showed a significant reduction in net photosynthesis and stomatal conductance but did not differ from control leaves in all the chemical parameters analysed. Nevertheless, leaf decomposition rate was lower in treated leaves. The main differences between the models describing the mass loss in exposed and control leaves were played by ADF for exposed leaves and by lignin for control leaves, as well as by N, that showed a greater contribution in the model for the exposed leaves. Ozone fumigation of Q. ilex results in leaf litter decomposition slowing down, mainly due to ADF joint dynamics with the other variables describing mass decay, even if no detectable changes in initial leaf composition occur.
The following values have no corresponding Zotero field: pub-location: 22 RUE DE PALESTRO, PARIS, 75002, FRANCE publisher: SPRINGER FRANCE
Keywords: decomposition; Leaf chemistry; Litter bags and mesocosms

Ranges of nutrient concentrations in Quercus ilex leaves at natural and urban sites - Maisto, Giulia; Baldantoni, Daniela; De Marco, Anna; Alfani, Anna; De Santo, Amalia Virzo (JOURNAL OF PLANT NUTRITION AND SOIL SCIENCE, 2013)
The leaf nutrient concentrations and the N-to-nutrient ratios were analyzed to evaluate the nutritional status of holm oaks (Quercus ilex L.) experiencing various anthropogenic pressures. Leaves (1 year old) of Q. ilex and surface soil (0-5cm) surrounding the trees were collected at seven natural and seven urban sites in Campania Region (Southern Italy) and analyzed for the concentrations of macro (C, N, P, S) and micronutrients (Mn, K, Na, Cu, Mg, Ca, Fe, Zn). The available soil fraction of micronutrients was also evaluated. The nutrients showed different concentration ranges for the natural and the urban sites in the soil (total and available) and in the leaves, that we reported separately. Organic-matter content and macronutrient concentrations were higher in the natural soils, while the highest leaf N, S, and P concentrations were found at some urban sites. Concentrations of Cu, Na and Zn both in leaves and soil, and Mg and Fe in leaves from the urban sites appeared to be affected by air depositions. Manganese was the only micronutrient to show higher concentrations at the natural than at the urban sites, both in soil and leaves. For this nutrient, in addition, a relationship between leaf and available soil concentrations was found at the natural sites. The ratios between the concentrations of N and each studied nutrient in the leaves highlighted a different nutritional status between the plants from the natural and urban sites.
Keywords: Campania Region; Holm oak; leaf N-to-nutrient ratios; southern italy; total and available soil nutrient concentrations

Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

Leaves of Quercus ilex L. as biomonitors of PAHs in the air of Naples (Italy) - Alfani, Anna; Maisto, Giulia; Vittoria Prati, Maria; Baldantoni, Daniela (Atmospheric Environment, 2001)
Polycyclic aromatic hydrocarbons (PAHs)were determined by the GC-MS chromatography in the leaves of Quercus ilex L., an evergreen Mediterranean oak, to monitor the degree of pollution in the urban area of Naples compared to remote areas. Leaf samples were collected in July 1998 from four urban parks, six roadsides and two sites in remote areas. The total PAH contents in Q. ilex leaves ranged from 106.6 in a control site to 4607.5 ng/g d.w. along a road with a high tra$c #ow. The mean concentration factors (urban/control)were 3.8 for the parks and 15 for the roads. The contribution of carcinogenic PAHs (benz[a]anthracene, benzo[b]#uoranthene, benzo[k]#uoranthene, benzo[a]pyrene, dibenz[a,h]anthracene, indeno[1,2,3-c,d]pyrene)was higher in urban area and di!ered according to the site, ranging from 6.7% to 21.3%. The total PAH burden in control sites was dominated by the low molecular weight PAHs, whilst along the urban roads #uoranthene, pyrene and benz[a]anthracene among the measured PAHs showed the highest values. PAHs were positively correlated (P(0.01)to trace metals measured in a previous study.
Keywords: biomonitoring; leaves; polycyclic aromatic hydrocarbons; Quercus ilex L; rural and urban areas

Leaves of Quercus ilex L. as biomonitors of PAHs in the air of Naples (Italy) - Alfani, Anna; Maisto, Giulia; Vittoria Prati, Maria; Baldantoni, Daniela (Atmospheric Environment, 2001)
Polycyclic aromatic hydrocarbons (PAHs)were determined by the GC-MS chromatography in the leaves of Quercus ilex L., an evergreen Mediterranean oak, to monitor the degree of pollution in the urban area of Naples compared to remote areas. Leaf samples were collected in July 1998 from four urban parks, six roadsides and two sites in remote areas. The total PAH contents in Q. ilex leaves ranged from 106.6 in a control site to 4607.5 ng/g d.w. along a road with a high tra$c #ow. The mean concentration factors (urban/control)were 3.8 for the parks and 15 for the roads. The contribution of carcinogenic PAHs (benz[a]anthracene, benzo[b]#uoranthene, benzo[k]#uoranthene, benzo[a]pyrene, dibenz[a,h]anthracene, indeno[1,2,3-c,d]pyrene)was higher in urban area and di!ered according to the site, ranging from 6.7% to 21.3%. The total PAH burden in control sites was dominated by the low molecular weight PAHs, whilst along the urban roads #uoranthene, pyrene and benz[a]anthracene among the measured PAHs showed the highest values. PAHs were positively correlated (P(0.01)to trace metals measured in a previous study.
Keywords: biomonitoring; leaves; polycyclic aromatic hydrocarbons; Quercus ilex L; rural and urban areas